Heading in football, long-term cognitive decline and dementia: evidence from screening retired professional footballers - Vann Jones, S. A.; Breakey, R. W.; Evans, P. J. (British Journal of Sports Medicine, 2014)
Background: Heading impairs cognition in the short and medium-terms; however, little is known about the long-term consequences. This study aimed to investigate the hypothesis that chronic low-level head trauma is associated with persistent cognitive decline. Methods All members of Former Player Associations (FPAs) from four professional football clubs in the UK were contacted to participate in the study. Participants were required to complete a self-assessed test of cognition, the Test Your Memory questionnaire. Further information was collected from respondents in order to analyse the potential effect of a number of variables on cognition. Results: 10 of 92 respondents (10.87%) screened positive for possible mild cognitive impairment (MCI) or dementia. There was no association between low-risk and high-risk playing positions (HR=0.40, p=0.456) or length of playing career (HR=1.051 95% CI 0.879 to 1.257, p=0.586) and a positive screening result. Age was a risk factor (HR=1.137 per additional year, 95% CI 1.030 to 1.255, p<0.05), although this was not significantly different from the population prevalence across age groups. Conclusions These results suggest that once a player ends their playing career, their risk of harm falls in line with the population, suggesting either that changes are reversible or that heading may not be as harmful as commonly thought. Future longitudinal studies of large numbers of professional football players are needed to support the findings from this study.